PENGEMBANGAN MODEL ACTIVE LEARNING ICARE SYSTEM PADA PEMBELAJARAN MATEMATIKA UNTUK SISWA KELAS VII - Mahroji Mahroji (Devosi : Jurnal Teknologi Pembelajaran, 2015)
Abstract: This study aims to produce a product of ICARE model active learning system in the form of learning implementation plan (RPP), student worksheet (LKS) and tools evaluation on social arithmetic material. This learning model is in accordance with the 2013 curriculum requires a student-centered learning because the steps are: introduction, connection, application, reflection, extension allows students were very active. Stages of development of this model begins with an analysis of the content and instructional design with the validation process by experts. Analysis of product testing through field observations by two teachers of mathematics, analysis of student questionnaire responses on whether or not interesting learning model was developed, and analysis of student learning outcomes. The conclusions of the analyzes above, that the model active learning system developed ICARE very viable means of learning model is very effective for implement in the learning of mathematics students of class VII SMP Negeri 3 Sidoarjo on Social Arithmetic material. Keywords: Model pembelajaran, Active Learning ICARE System, Material, Social Arithematic